The development of orchard fruit-growing in Poland in the period of impact of the Common Agricultural Policy. Production-related and spatial issues - Wójcik, Marcin; Traczyk, Anna (Bulletin of Geography. Socio-economic Series, 2020)
In the early 21st century, orchard fruit-growing is one of Poland’s most rapidly-growing branches of agriculture. The rate and direction of this process of development have obviously been under the fundamental influence of an European Union Common Agricultural Policy (CAP) binding upon Poland since 2004. A series of changes concerning orchard fruit-growing have been ushered in this way, with production intensifying and spatial reorganisation taking place. The work described here has thus sought to determine changes in the level of output achieved by fruit-growing, as well as changes in the distribution of orchards, during the time over which the CAP’s instruments have been exerting their influence on Polish agriculture. Research first concentrated on identification of the key CAP instruments capable of influencing the development of orcharding in Poland. Analyses were then carried out in respect of changes in the level of fruit production and the area devoted to orchard cultivation. Impacts on production, including those manifested in increased exports of fresh fruit, are shown to have helped Poland maintain position on European and world markets, with consequences including an increased area assigned to the growing of the most in-demand fruit (i.e. apples and raspberries), in peripheral regions especially. This can therefore be thought to reflect both growing specialisation in farming, and a way of maintaining some economic vitality in rural areas far from large urban agglomerations.